Crystal structure of isoxazolo[4,5-b]pyridin-3-amine, C6H5N3O - Wang Litong; Wang Jinfang; Meng Fanchao; Zheng Xiaoxin; Han Quanxiang (Zeitschrift für Kristallographie - New Crystal Structures)
C6H5N3O, monoclinic, P21/n (no. 14), a = 5.2140(2) Å, b = 6.8527(2) Å, c = 16.3538(5) Å, β = 97.335(3)°, V = 579.54(3) Å3, Z = 4, Rgt (F) = 0.0336, wRref (F 2) = 0.0881, T = 293(2) K.